Análisis de la gestión recaudadora de la cartera de impuestos administrados por el Gobierno Autónomo Descentralizado Municipal del cantón Tosagua - Cedeño Vera, Nicole Jamileth (2024)
The research was carried out with the purpose of analyzing the collection management of the tax portfolio administered by the Municipal Autonomous Decentralized Government of the Tosagua Canton for the identification of improvement actions that contribute to efficiency in the management of the institution, period 2019-2022. The development of this objective was carried out through the use of analysis, synthesis, deduction, induction and historical methods, applied in the execution of three methodological phases: first, the current situation of tax collection management is determined. . carrying out the historical and comparative analysis of the amounts collected in the study period, in addition, an interview was conducted with the person responsible for the area to identify weaknesses and strengths in management; The efficiency measurement was then carried out through the design and application of indicators, whose acceptance criteria were defined using the traffic light technique; As for the third phase, an action plan was proposed through the 5W+1H matrix, based on the problem identified through the Ishikawa diagram. The results determine that tax collection management is inefficient, because in none of the years of study has it managed to meet the projected collection. It is concluded that the institution requires important improvements in tax collection management, mainly in effective collection planning, in addition to the design and dissemination of strategies that encourage the payment of taxes by taxpayers.